Gestational Influenza Increases the Risk of Psychosis in Adults - Cai, Lei; Wan, Chun-Lin; He, Lin; Jong, Simone d.; Chou, Kuo-Chen (Medicinal Chemistry, 2015)
Psychotic disorders are complex and caused by interplay of genetic and environmental factors. Influenza is a common infectious disease in humans, and it has been suggested that maternal influenza is an estimated risk factor for psychotic disorders, especially for schizophrenia. In view of conflicting results of this association in literature, we performed the strict meta-analysis to examine whether maternal influenza is a risk factor for psychosis in the children. Four ecological studies and three birth cohort studies were included in our meta-analysis. It has been observed that the Risk Ratio (RR) of maternal influenza on psychosis is 1.062 (95% Confidence Interval (CI) = 1.004-1.123) for the analysis of ecological studies and the RR is 1.564(95%CI=1.051-2.324) for the analysis of birth cohort studies. Furthermore, a survey of pregnant women and fetus’ health in Nanjing of China indicated that only 1.5% of women received the influenza vaccine before pregnancy, 0.4% received it during pregnancy, and 5.1% were willing to receive the influenza vaccine if necessary. These results showed that gestational influenza could increase mental disorders risks in adult offspring besides its established harms for gravidas. Results suggest it might be effective to increase attention to gravidas to protect them from influenza infection through encouragement of vaccinations.
Keywords: influenza